Changing bodies, degenerating output: phases of Basic Education in Nigeria from 1914 to 2014 - Grace Oluremi Akanbi (Cadernos de História da Educação)
Abstract This paper focuses the administration of basic education in Nigeria under different administrative bodies from 1914 to 2014. It identifies the various bodies that were responsible for managing basic education at different dispensations and why they were established. This study is historical, and historical method is employed. Both primary and secondary sources of information were explored to get relevant materials for the study. It was discovered in the course of the study that the bodies were just changing names as the output continues to degenerate in Basic Education. Therefore, it is recommended among others that; basic education should be devoid of politics for effective planning, community participation should be incorporated and, more and adequate infrastructural facilities should be provided in the primary schools. Key words: Educational bodies, basic education, implementation.